The role of parental incarceration in predicting trajectories of child internalizing problems. (August 2020) - Kjellstrand, Jean; Yu, Gary; Eddy, J. Mark; Clark, Miriam; Jackson, Arriell
Highlights: The study examines how parental incarceration predicts trajectory membership. Earlier research identified four developmental trajectories for internalizing behaviors. One normative low risk pathway and three problematic pathways were identified. Parental incarceration was not a key predictor for any of the pathways. However, the study identified other significant predictors of trajectory membership. Parental incarceration serves as a risk marker for internalizing problems for youth. Abstract: On any given day, millions of U.S. children have at least one parent in jail or in prison. As the number of children facing this situation has increased considerably over the past several decades, interest has intensified regarding the impact of this experience on child adjustment. Although substantial research has focused on the link between parental incarceration and child externalizing behaviors, comparatively little research has examined the impact of parental incarceration on child internalizing problems across time. This leaves a critical gap in understanding child outcomes as a whole, as internalizing problems can have implications for psychopathology and other problematic issues not only across childhood but also across adulthood. To address this gap, the effects of parental incarceration on developmental trajectories of internalizing problems were examined while controlling for key individual, parental and family influences. Using four trajectory groups – Low-Stable, Preadolescent-Limited, Moderate-Increasing, and High-Decreasing – found in previous analyses of data from a longitudinal study of 655 youth, we fit unadjusted and adjusted multinomial logistic regression models. The models included all predictors of interest on the categorical outcome of the specific internalizing problem trajectory using the Low-Stable individuals as the reference group. Study results suggest that when controlling for other family risks, parental incarceration is not a significant risk factor for any of the trajectories in the development of internalizing problems. These findings provide evidence that parental incarceration may be a risk marker, rather than a unique risk factor, for internalizing problems among youth.